ETHNIC AND POPULATION-SPECIFIC FEATURES OF SOME IMMUNOLOGICAL PARAMETERS IN CHRONIC HELICOBACTER PYLORI INFECTION - E. S. Ageeva; V. M. Iptyshev; O. V. Stygasheva; N. V. Ryasantseva (Медицинская иммунология, 2014)
Abstract. Immunophenotype profile of lymphocytes (CD3+, CD4+ and CD8+) from peripheral blood in gastric ulcer associated with Helicobacter pylori, chronic gastritis and stomach cancer has been studied in Khakassian aboriginals and migrants. Apoptosis of peripheral blood lymphocytes was also evaluated. Some alterations of immunological indexes were revealed in patients infected with Helicobacter pylori, as compared to healthy donors and migrants. The changes were characterized by a more intense apoptotic death of lymphocytes in the patients, when compared with numbers of apoptotic cells in control group. Probable role of apoptotic events in regulation of local and system immunity in Helicobacter pylori infection is discussed.